The Image of Hindu Women in Conducting Their Swadharma - Ni Kadek Ayu Kristini Putri; Ni Made Sukrawati; Desak Nyoman Seniwati; I Gusti Ayu Ngurah; Ni Ketut Sukiani (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
Women are creatures that are identical with the symbols of the world, as a balancer for the entire universe, women is discussed from era to era, from the Krtayuga era to the present, much debated era, the Kaliyuga era. Women are still discussed especially with regard to their inner and outer forms. To produce valid and reliable data, this research uses qualitative research methods. To produce logical data, this article performs several stages of data sorting as follows: 1). Data reduction, 2). Data display, 3). Data verification and, 4). Data interpretation from the articles. Related references really support the validity of a scientific work, therefore library techniques are also used through literature exploration on Google Scholar. The unique story of a creature named a woman is still a mystery by the analogy of men. The behavior of women from the incarnation of God who is born from a mother conceives that the woman is indeed a balancer both from bhuana agung and bhuana alit, the role and nature of a woman is very much different from that of men, starting from giving birth to regeneration - men do not can do this - but with the absence of men, women will also not be able to give birth to a baby. Hindu women who play a lot of roles in all their practices and customs, exhaust their minds and energy to live this attachment. Not to mention the modern era that is entangled in the economy and fashion in the social media era. Can Hindu women manage their lives for things like that? To be a career woman or traditional woman are not an easy thing to do, the consequences in living it are always there and the risk in every decision will give birth to pros and cons, and Hindu women, who are discussed in this article, are hoped to persist in every era while maintaining a positive image for Hindu women in carrying out their swadharma (obligation).